The Council of All Beings - Christidis, Yiannis (My University, 2026)
Documentary, 34'. Deliverable 5.4 of the Creative Europe Program. This is the last call for all beings, to gather up and learn to think like a mountain, in order to live a bit better and longer. Set in Cyprus, this hybrid satirical documentary unveils few unfriendly - towards the non-humans- behaviors, sets and assets, while commenting on the role of the artists.